THE INFLUENCE OF THE USE OF INFORMATION AND ORGANIZATIONAL COMMUNICATION TECHNOLOGY ON THE PERFORMANCE OF VILLAGE APPARATUS IN PASIR DISTRICT EAST LAMPUNG SAKTI - Fauzi, Fauzi; Aliyah, Hikmatul; Qomariyah, Nurul; Sugiono, Sugiono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
In this context, research on the impact of training and employment incentives on the performance of Siskeudes operators in the district of Seketar, East Lampung becomes important. This research will look at whether the training given to Siskeude operators has a positive impact on their performance. In addition, the research will also dig into the influence of employment inducements on Siskeudas operators' performance in that district. This research uses descriptive quantitative methods. The data collection technique in this study is a questionnaire with samples of 17 respondents using saturated sampling techniques. The data analysis technique used in this study is simple regression with the help of the SPSS 16 application. The results of this study suggest that job training variables have a positive and significant impact on employee performance. The correlation factor was 67.3%, while the remaining 32.7% was influenced by other factors that were not included in the study. Keywords: Training, Incentive, Performance